Water Subsidy Policies : Comparison of the Chilean and Colombian Schemes - Gomez-Lobo, Andres; Contreras, Dante (Washington, DC: World Bank, 2014)
Analysis of two water subsidy schemes a means tested subsidy in Chile and a geographically targeted subsidy in Colombia shows that the means-tested system is better able to identify poor households than the geographically targeted scheme. However, the overall distributive impact of both schemes is quite similar, at least for the three lowest income deciles, because the amount of benefits per household in the geographically targeted Colombian scheme are differentiated by the socioeconomic classification of household. Despite the relative merits of the Chilean means tested scheme, targeting errors are still quite large. More than 60 percent of subsidies accrue to households that are above the third decile of the income distribution. If the policy objective in Chile is to benefit a significant proportion of households in the lowest income deciles, then either the targeting mechanism must be improved or the number of subsidies has to increase to take into account these targeting imperfections. In Colombia almost all households receive some kind of benefit, implying an unnecessarily high fiscal cost. An improvement in the targeting mechanism could lower this cost without jeopardizing benefits to lower-income households. Some suggestions for additional research and for improving both schemes are discussed.